Cost of adverse events during treatment with everolimus plus exemestane or single-agent chemotherapy in patients with advanced breast cancer in Western Europe. (December 2014) - Campone, Mario; Yang, Hongbo; Faust, Elizabeth; Kageleiry, Andrew; Signorovitch, James E.; Zhang, Jie; Gao, Haitao
Abstract Objective: Treatment options for recurrent or progressive hormone receptor-positive (HR+) advanced breast cancer include chemotherapy and everolimus plus exemestane (EVE + EXE). This study estimates the costs of managing adverse events (AEs) during EVE + EXE therapy and single-agent chemotherapy in Western Europe. Methods: An economic model was developed to estimate the per patient cost of managing grade 3/4 AEs for patients who were treated with EVE + EXE or chemotherapies. AE rates for patients receiving EVE + EXE were collected from the phase III BOLERO-2 trial. AE rates for single-agent chemotherapy, capecitabine, docetaxel, or doxorubicin were collected from published clinical trial data. AEs with at least 2% prevalence for any of the treatments were included in the model. A literature search was conducted to obtain costs of managing each AE, which were then averaged across Western European countries (when available). Per patient costs for managing AEs among patients receiving different therapies were reported in 2012 euros (€). Results: The EVE + EXE combination had the lowest average per patient cost of managing AEs (€730) compared to all chemotherapies during the first year of treatment (doxorubicin: €1230; capecitabine: €1721; docetaxel: €2390). The most costly adverse event among all patients treated with EVE + EXE was anemia (on average €152 per patient). The most costly adverse event among all patients treated with capecitabine, docetaxel, or doxorubicin was lymphocytopenia (€861 per patient), neutropenia (€821 per patient), and leukopenia (€382 per patient), respectively. Conclusions: The current model estimates that AE management during the treatment of HR+ advanced breast cancer will cost one-half to one-third less for EVE + EXE patients than for chemotherapy patients. The consideration of AE costs could have important implications in the context of healthcare spending for advanced breast cancer treatment.